Answer:
Adjacent. x is 100.
Step-by-step explanation:
Answer: 1
Step-by-step explanation:
All you had to do was multiply g by 1 so f(g(1)) as a value is 1
Mean is when you take all the numbers and add them together and divide by the amount of numbers there
Example: Find the mean of :3,4,6,7
So you a 3+4+6+7=20 divide that by 4(because there you added 4 numbers) and that equals 5
ANSWER
![y= -3{(x + 4)}^{2} + 2](https://tex.z-dn.net/?f=y%3D%20-3%7B%28x%20%2B%204%29%7D%5E%7B2%7D%20%20%2B%202)
EXPLANATION
The given function is:
![y= -3x^2-24x-46](https://tex.z-dn.net/?f=y%3D%20-3x%5E2-24x-46)
Factor -3 for the first 2 terms.
![y= -3(x^2 + 8x)-46](https://tex.z-dn.net/?f=y%3D%20-3%28x%5E2%20%2B%208x%29-46)
We add and subtract the square of the coefficient of x.
![y= -3(x^2 + 8x + {(4)}^{2} ) - - 3( {4)}^{2} -46](https://tex.z-dn.net/?f=y%3D%20-3%28x%5E2%20%2B%208x%20%2B%20%20%7B%284%29%7D%5E%7B2%7D%20%29%20%20-%20-%203%28%20%7B4%29%7D%5E%7B2%7D%20-46)
Factor the perfect square trinomial.
![y= -3 {(x + 4)}^{2} ) + 48 -46](https://tex.z-dn.net/?f=y%3D%20-3%20%7B%28x%20%2B%204%29%7D%5E%7B2%7D%20%29%20%20%2B%2048%20-46)
The vertex form is:
![y= -3{(x + 4)}^{2} + 2](https://tex.z-dn.net/?f=y%3D%20-3%7B%28x%20%2B%204%29%7D%5E%7B2%7D%20%20%2B%202)
![\mathfrak{\huge{\pink{\underline{\underline{AnSwEr:-}}}}}](https://tex.z-dn.net/?f=%5Cmathfrak%7B%5Chuge%7B%5Cpink%7B%5Cunderline%7B%5Cunderline%7BAnSwEr%3A-%7D%7D%7D%7D%7D)
Actually Welcome to the Concept of the Functions.
Let's first find the g(-1),
so we get as
3(-1)^2 +5(-1)-6
=> 3 -5-6
=> -8
now since g(-1) =-8
let's find f(g(-1)) that is f(-8)
f(-8) = 4(-8) + 14
=> f(g(-1)) = -32+14
=> f(g(-1)) = -18
-18 is the answer.